Cross border of Jurisdiction between Arbitration and District Court in Business Dispute Settlement under the Indonesian Legal System - Fakhriah, Efa Laela; Afriana, Anita (Universitas Lampung, 2023)
In principle, the settlement of business disputes in Indonesia can be done amicably either through the court or outside the court. The court proceeding usually takes a long time, impacting overall case costs in comparison to dispute settlement outside the court. Arbitration as an alternative dispute resolution offers advantages compared to mediation, conciliation, and negotiation as it has an identical adjudicative nature to court proceedings. Therefore, arbitration is the preferred method for settling business disputes due to its perceived effectiveness and efficiency, resulting in win-win solutions. In addition, within the Indonesian legal framework, arbitration closely parallels court proceedings for dispute resolution, and its decisions carry the same level of binding authority and enforceability. This article relies on secondary data analyzed using a qualitative-juridical method to examine the jurisdiction of district court and arbitration. The findings reveal that arbitration has absolute jurisdiction when there exists an arbitration clause or an underlying arbitration agreement, thereby excluding the jurisdiction of the district court.